Complete Genome Sequence of “Candidatus Portiera aleyrodidarum” BT-QVLC, an Obligate Symbiont That Supplies Amino Acids and Carotenoids to Bemisia tabaci - Santos-Garcia, Diego (American Society for Microbiology, 2012)
The genome of “Candidatus Portiera aleyrodidarum,” the primary endosymbiont of the whitefly Bemisia tabaci (Mediterranean species), is reported. It presents a reduced genome (357 kb) encoding the capability to synthetize, or participate in the synthesis of, several amino acids and carotenoids, being the first insect endosymbiont capable of supplying carotenoids.